Informed Consent, Autonomy, and the Death of Therapeutic Privilege: Clinical, Bioethical, and Legal Perspectives - John Doyle (Association of American Medical Colleges, 2008)
Abstract This case-based educational module is intended to introduce medical students to some of the central issues in medical ethics. The module begins with four clinical cases for the students to consider. This is followed by an introduction to the principles of medical ethics as well as some relevant case law. The four cases are then discussed from the perspective of the various principles and legal cases provided. The central objective of the module is to introduce students to the concepts of informed consent, patient autonomy, and therapeutic privilege through a discussion of the clinical scenarios. This resource was developed as a supplement to classroom and one-on-one teaching of ethical issues to medical students and residents at the Cleveland Clinic. This educational resource is not without potential limitations. First, it casts issues in a traditional western ethical framework that may be inappropriate for some cultures where the concept of personal autonomy is not emphasized. Second, at least to a limited extent, it inevitably reflects my own personal views and biases accumulated over two decades of clinical practice.